DEVELOPING HALAL VACCINE PRODUCTION IN INDONESIA: CHALLENGES AND FUTURE OPPORTUNITIES - Mujahidin Ahmad (El-Hayah, 2022)
When the Covid19 pandemic occurred, Indonesia was the largest country in Southeast Asia with the most positive confirmed victims and the highest death rate. The consequences of the government's efforts to prevent the government from ordering vaccines reached 450 million doses for 187 million people in order to achieve individual immunity and herd immunity. As a country with the largest Muslim population in the world, the halal status of vaccines is very important. Of the six types of vaccines in Indonesia, namely; only the Sinovac vaccine received halal status, while other vaccines such as AstraZeneca, Pfizer, Moderna, Sinofarm were ultimately still used for emergency reasons due to insufficient halal vaccines. In the future, Muslim countries need to continue to develop alternative technologies and materials to ensure that the vaccines given are halal. Use of cell lines to produce vaccines such as Vero (Monkey), MDCK (Dog), BHK21 (Hamster), HEK (Human), PER (Human). The medium used for cell growth (upstream process) also contains Human Blood (HuS), Horse Blood (HS), Cow Blood (FBS). Likewise, the use of Pig and Animal Trypsin that is not slaughtered in a halal way, as well as the use of stabilizers in vaccine formulations such as Human or bovine (cow) Serum, Porcine or Cow Gelatin, Ethanol are critical points for fatwa institutions such as not passing the halal category. The use of alternative materials in vaccine production such as insect cells, yeast, fungi, non-animal medium and vegetable stabilizers has the opportunity to replace mainstream materials. The independence of halal vaccine production provides an opportunity to increase national resilience.